2011
DOI: 10.1186/2047-783x-16-10-457
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the state version questionnaire on autonomic regulation (state-aR) for cancer patients

Abstract: ObjectivesCurrent quality of life inventories used in oncology mainly measure the effects of chemo- or radiotherapy alongside functional and role scales. A new approach is to measure the autonomic state of regulation with the trait-inventory of autonomic regulation (Trait-aR). Loss of Trait-aR has been shown in different medical conditions such as breast cancer (BC) but not in colorectal cancer patients (CRC). In this paper we report the validation of a new state autonomic regulation scale (State-aR) of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Our findings on self-regulation are consistent with results of another research group that found that self-regulation is positively associated with patients survival with a range of solid tumours [ 11 , 19 ]. Self-Regulation (SR) is thought to represent the "ability to actively achieve well-being, inner equilibrium, appropriate stimulation and feeling of competence to control and manage stressful situations"[ 20 ] and shows repeatedly low-moderate correlations with aR (0.30-0.38) [ 25 , 20 ]. Unpublished data from our study group show a strong correlation between SR and the three SOC-subscales (comprehensibility, manageability and meaningfulness) from r = 0.70 to 0.73 (p < 0.05) which suggest that SOC/resilience might be connected with a goal-orientated change of lifestyle and orientation towards wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on self-regulation are consistent with results of another research group that found that self-regulation is positively associated with patients survival with a range of solid tumours [ 11 , 19 ]. Self-Regulation (SR) is thought to represent the "ability to actively achieve well-being, inner equilibrium, appropriate stimulation and feeling of competence to control and manage stressful situations"[ 20 ] and shows repeatedly low-moderate correlations with aR (0.30-0.38) [ 25 , 20 ]. Unpublished data from our study group show a strong correlation between SR and the three SOC-subscales (comprehensibility, manageability and meaningfulness) from r = 0.70 to 0.73 (p < 0.05) which suggest that SOC/resilience might be connected with a goal-orientated change of lifestyle and orientation towards wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…It includes items adapted from the trait version to reflect state of regulations in relation to the preceding week. Although an 18-item state version has been published, 58 only the 14 items that could be adapted and that were not too specific were used. Each trait aR item was scored on a 3-point scale (though the anchors differed across items) whereas each state aR item was scored on a 5-point scale (with different anchors across items).…”
Section: Methodsmentioning
confidence: 99%
“… 59 Scores have been shown to have adequate-to-good internal consistency, test-retest reliability, and validity among adults with a range of medical conditions, including cancer. 57 - 59 …”
Section: Methodsmentioning
confidence: 99%
“…Patients were also given a number of questionnaires before and after the intervention, including State-autonomic Regulation (S-aR), 11 Self-regulation (SR), 12 , 13 Internal Coherence Scale (ICS), 14 and the Herdecke Quality of Life Questionnaire (HLQ). 15 At the start of the study, patients also were given the questionnaire on Trait-autonomic Regulation (T-aR).…”
Section: Methodsmentioning
confidence: 99%
“…16 The S-aR questionnaire is a four-dimensional, 18-item inventory with the subscales orthostatic-circulatory, rest/activity, thermo-sweating, and digestive regulation. 11 The T-aR questionnaire is a three-dimensional, 18-item inventory with the subscales orthostatic-circulatory, rest/activity, and digestive regulation. 16 The autonomic regulation records the integration of endogenous autonomic functions, such as sleeping, waking, vertigo, orthostasis, and thermal and digestive regulation as well as intrinsic motivation.…”
Section: Original Research Patients and Methodsmentioning
confidence: 99%